Blood transfusion in preterm infants improves intestinal tissue oxygenation without alteration in blood flow. Issue 4 (10th August 2016) - Banerjee, J.; Leung, T. S.; Aladangady, N.
Abstract : Background and Objective: The objective of the study was to investigate the splanchnic blood flow velocity and oximetry response to blood transfusion in preterm infants according to postnatal age. Materials and Methods: Preterm infants receiving blood transfusion were recruited to three groups: 1–7 (group 1; n = 20), 8–28 (group 2; n = 21) and ≥29 days of life (group 3; n = 18). Superior mesenteric artery (SMA) peak systolic (PSV) and diastolic velocities were measured 30–60 min pre‐ and post‐transfusion using Doppler ultrasound scan. Splanchnic tissue haemoglobin index (sTHI), tissue oxygenation index (sTOI) and fractional tissue oxygen extraction (sFTOE) were measured from 15–20 min before to post‐transfusion using near‐infrared spectroscopy. Results: The mean pretransfusion Hb in group 1, 2 and 3 was 11, 10 and 9 g/dl, respectively. The mean (SD) pretransfusion SMA PSV in group 1, 2 and 3 was 0·63 (0·32), 0·81 (0·33) and 0·97 (0·40) m/s, respectively, and this did not change significantly following transfusion. The mean (SD) pretransfusion sTOI in group 1, 2 and 3 was 36·7 (19·3), 44·6 (10·4) and 41·3 (10·4)%, respectively. The sTHI and sTOI increased ( P < 0·01), and sFTOE decreased ( P < 0·01) following transfusion in all groups. On multivariate analysis, changes in SMA PSV and sTOI following blood transfusion were not associated with PDA, feeding, pretransfusion Hb and mean blood pressure. Conclusion: Pretransfusion baseline splanchnic tissue oximetry and blood flow velocity varied with postnatal age. Blood transfusion improved intestinal tissue oxygenation without altering mesenteric blood flow velocity irrespective of postnatal ages.